Multilocus Sequence Typing and Virulence-Associated Gene Profile Analysis of Staphylococcus aureus Isolates From Retail Ready-to-Eat Food in China - Yang, Xiaojuan; Yu, Shubo; Wu, Qingping; Zhang, Jumei; Wu, Shi; Rong, Dongli (Frontiers in Microbiology, 2018)
The aim of this study was to characterize the subtypes and virulence profiles of 69 Staphylococcus aureus isolates obtained from retail ready-to-eat food in China. The isolates were analyzed using multilocus sequence typing (MLST) and polymerase chain reaction (PCR) analysis of important virulence factor genes, including the staphylococcal enterotoxin (SE) genes (sea, seb, sec, sed, see, seg, seh, sei, sej), the exfoliative toxin genes (eta and etb), the toxic shock syndrome toxin-1 gene (tst), and the Panton-Valentine leucocidin-encoding gene (pvl). The isolates encompassed 26 different sequence types (STs), including four new STs (ST3482, ST3484, ST3485, ST3504), clustered in three clonal complexes and 17 singletons. The most prevalent STs were ST1, ST6, and ST15, constituting 34.8% of all isolates. Most STs (15/26, 57.7%) detected have previously been associated with human infections. All 13 toxin genes examined were detected in the S. aureus isolates, with 84.1% of isolates containing toxin genes. The three most prevalent toxin genes were seb (36.2%), sea (33.3%), and seg (33.3%). The classical SE genes (sea–see), which contribute significantly to staphylococcal food poisoning (SFP), were detected in 72.5% of the S. aureus isolates. In addition, pvl, eta, etb, and tst were found in 11.6%, 10.1%, 10.1%, and 7.2% of the S. aureus isolates, respectively. Strains ST6 carrying sea and ST1 harboring ec-seh enterotoxin profile, which are the two most common clones associated with SFP, were also frequently detected in the food samples in this study. This study indicates that these S. aureus isolates present in Chinese ready-to-eat food represents a potential public health risk. These data are valuable for epidemiological studies, risk management, and public health strategies.